Respuesta :

Answer:

C and F

Step-by-step explanation:

You have to get everything on one side of the equation and then throw it into the quadratic formula.  The equation in standard form is

[tex]x^2-6x-2=0[/tex]

Plugging into the quadratic formula gives you this:

[tex]x=\frac{6+/-\sqrt{(-6)^2-4(1)(-2)} }{2(1)}[/tex]

Simplifying that gives you:

[tex]x=\frac{6+/-\sqrt{44} }{2}[/tex]

The square root of 44 simplifies so we have this:

[tex]x=\frac{6+/-2\sqrt{11} }{2}[/tex]

which then simplifies finally to:

[tex]x=3+/-\sqrt{11}[/tex]

So the 2 solutions are

[tex]x=3+\sqrt{11}[/tex]  and  [tex]x=3-\sqrt{11}[/tex]